Career after Retirement - Diminishing Abilities or Diminishing Opportunities? - T. S. Sudheeran
Like work, retirement means different things to different persons. For some, it is the point of extinction in one’s career life; but for others it is the beginning of a second career. Theoretically, there are four main conceptualizations (Wang, M. & Schultz, K.S., 2009) held by scholars to deal and explain the transition that has been happening to an individual’s life after retirement. For convenience the study here focused on retirement as an adjustment process where it examines the issues and challenges faced by retirees in their post-retirement career life. With the changes in the socio- economic realm there occurred a gradual change in the demography of the labour force. Though it is remarkably different across regions and sectors, it has relevance both in developed and developing economies. Considering the importance of the situation, both public and private organisations across the globe engaged in framing up policies and programme to deal with the diverse work force. Add to this, the idea of a successful retirement life gave impetus to concepts like bridge employment, flexible retirement, phased retirement, retirement planning, post-retirement career life, etc. Though the idea has been popularized and widely practiced among developed countries, it is still not been accepted in its fullest sense in our country due to the lack of interest and enthusiasm shown by both public and private agencies. Since the issue is multidimensional, the article attempts to explore and untangle the issues and challenges faced by retirees in their second career.